PLANKTON OF CALICUT INSHORE WATERS AND ITS RELATIONSHIP WITH COASTAL PELAGIC FISHERIES - Mukundan, C (Indian Journal of Fisheries, 2011)
Studies on the inshore plankton of Calicut waters and on the related hydrological featuies have been made in earlier years, and there have been attempts, in general terms or specifically, at correlating these with the fisheries of the area. From Homell and Nayudu (1924) who suggested that the oil sardine might be coming into the inshore waters to feed on the plankton there, various workers have followed this view. Particular mention may be made, in this regard, of the observations of Chidambaram and Menon (1945) who arrived at a positive correlation between the plankton and the pelagic fisheries of this area during the post-monsoon period; of George (1953) who demarcated the inshore plankton as "edible" and "non-edible" from the point of view offish food and marked the fact that the fishery season along the coast coincided with the period of abundance of "edible plankton", suggesting close relationship between the two; of Subrahmanyan (1959) who discussed the relationship of plankton production with fluctuations of oil sardine and mackerel landings on a month-to-month basis, finding broad correlation between standing crop of the plankton and total quantity of fish landed.